Implementation of Audio-Visual Media in Pie Learning in Elementary School - Annisa, Eti Nadiatun; Ramzi, Muhajirin; Sukarto, Sukarto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Implementation of Audio-Visual Media in PAI Learning in Elementary Schools. This research aims to determine PAI learning planning using audio-visual media. This research was conducted at SDN 1 Rempek on students in grades 4 and 5 in semester 2 of the 2023/2024 academic year. With a total of 55 students, namely 35 students in class 4 and 20 students in class 5. The method used in this research is field research, with a qualitative descriptive approach, the subjects in this research are audio-visual media using LCD, teachers and also students. In this research, data collection techniques use interview, observation and documentation techniques, and data analysis techniques in this research use data condensation, data presentation and drawing conclusions. The results of this research show that Islamic Religious Education learning planning using audio-visual media in grades 4 and 5 is going well, this can be seen from the learning planning which is made in the form of teaching modules.